A study of the thermal degradation of an amine-cured epoxide resin at temperatures below 350 degrees C - Patterson-Jones, C.; Smith, D. A. (College of Aeronautics, 1967)
An epoxy resin made by the reaction of the diglycidyl ether of bis-phenol A and diaminodiphenyl methane was thermally degraded in vacuo at temperatures between 200°C and 350°C. The effect of degradation was examined by means of measurement of changes in the dielectric properties of the material and also by examination of compounds evolved by the cured resin. Definite evidence for the evolution of N-methyl aniline and N:N-dimethylaniline is advanced and added evidence for a dehydration reaction is put forward. Possible degradation mechanisms are discussed.